2017
DOI: 10.1108/ijmhsc-04-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

A case for a health promotion framework: the psychosocial experiences of female, migrant sex workers in Ireland

Abstract: Purpose The purpose of this paper is to examine the barriers preventing women in prostitution from accessing co-ordinated health services in the Republic of Ireland. By examining the experiences of migrant women engaged in prostitution, the research contributes to knowledge pertaining to the psychosocial experiences of female sex workers’ access to healthcare. Design/methodology/approach The study interviewed migrant women across Ireland, using a biographical narrative approach and an adapted voice-centred r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…That study included street and indoor parlour workers, yet sex work in Ireland has changed considerably since then, particularly with the rise of online sex work. Sweeney and Fitzgerald (2017) describe Irish sex work as having moved from brothel-based sex work and street work to escorting, with more isolated, independent and mobile working, with many sex workers travelling within Ireland to reach more customers. Their recent qualitative study on migrant sex workers' health found that fear of violence, robbery and refusal to pay for services 'combined with the need to remain invisible and on the margins due to their precarious legal status impacted migrant sex workers' health' (Sweeney and FitzGerald, 2017;Sweeney et al, 2019).…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
See 3 more Smart Citations
“…That study included street and indoor parlour workers, yet sex work in Ireland has changed considerably since then, particularly with the rise of online sex work. Sweeney and Fitzgerald (2017) describe Irish sex work as having moved from brothel-based sex work and street work to escorting, with more isolated, independent and mobile working, with many sex workers travelling within Ireland to reach more customers. Their recent qualitative study on migrant sex workers' health found that fear of violence, robbery and refusal to pay for services 'combined with the need to remain invisible and on the margins due to their precarious legal status impacted migrant sex workers' health' (Sweeney and FitzGerald, 2017;Sweeney et al, 2019).…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
“…Barriers to reporting are heightened for migrant sex workers with concern that contact with the police may lead to deportation or other immigration action for those with irregular or illegal status (Mai, 2009). Sweeney and FitzGerald (2017) found that female, migrant sex workers in Ireland feared reporting crimes and abuse they experienced to the Garda ı (the Irish police force) due to the risk of self-identifying as sex workers, their precarious legal status in Ireland (risk of potential deportation) as well as language difficulties.…”
Section: Prevalence and Nature Of Sex Work Victimisationmentioning
confidence: 99%
See 2 more Smart Citations
“…This limits their ability to access police protection, support services and other safety mechanisms (Visser et al, 2004). Criminalization impacts adversely sex workers’ lives beyond prostitution through threats of eviction and deportation (Sweeney and FitzGerald, 2017). The neo-abolitionist paradigm identifies groups who must become the focus for law reform and social control, namely ‘risky’ groups of purchasers and/or criminals and ‘at risk’ female sex workers.…”
Section: How Do Neo-abolitionists Demarcate Political Interaction On mentioning
confidence: 99%